Exploring Socio-Economic Characteristics on Adoption Intensity of Biochar Among Farming Households In Sub-Humid Regions of Western Kenya - Kyalo, Annastacia Maitha; Mogaka, Hezron; Kirimi, Florence Kaumi; Kizito, Kwena; Ndirangu, Samuel Njiri; Onyari, Charles Nyambane; Muriithi, Lydia; Elvin, Otara Nyaboe; Mutungi, Scholastica Katava; Kiprotich, Shadrack; Njiru, Moses Muchangi; Kamau, Ezekiel Areri (University of Embu, 2025)
Agriculture is a cornerstone of Kenya's economy, yet declining soil fertility and low adoption of sustainable agricultural technologies, such as biochar, have hindered productivity among smallholder farmers. Biochar is perceived to be a cost- effective technology especially among resource constraint farming households. Despite many smallholder farmers acknowledging the importance of biochar as a soil amendment, most farmers face socio-economic barriers that hinder its adoption at scale. This study focused on how socio-economic factors influence adoption intensity of biochar, with a focus on the farming households in the sub-humid regions of Western Kenya. Employing a multistage stratified sampling procedure and Heckman selection model, the study reveals that awareness of biochar, access to credits, total land used in farming and education level positively and significantly influences adoption of biochar while total land owned in acres negatively and significantly influences adoption of biochar. Similarly, awareness of biochar, access to credits, and education level positively and significantly influences adoption intensity of biochar while terms of land ownership negatively and significantly influence adoption intensity of biochar. The study identifies awareness of biochar, education, credit access, and land ownership as key factors influencing its adoption by smallholder farmers. Promoting biochar as a soil amendment and carbon sequestration technique for farmers should be the main goal of the government, non-governmental organizations, and development organizations. Promoting the advantages of biochar for crop yields and soil fertility should be spearheaded by the Ministry of Agriculture's Extension Department. While development organizations offer financial assistance and training to promote adoption, policymakers should push farmer cooperatives to reduce the cost of biochar production and implementation
Article
Keywords: Soil bulk density, microbial biomass carbon, inverse mills ratio, marginal effect, robust standard error.